Optimism and Pessimism during coronavirus pandemic & its relationship with psychological resilience on a sample of tenth grades students in Al-Sharqiya North at Sultanate of Oman - Al-Khawaja, Abdul Fattah Mohammed Saeed; Alshabibi, Issa ben Saleh ben Ahmaed (Journal of Educational and Psychological Sciences, 2021)
The present study was designed to determine the relationship between Optimism and Pessimism & its relationship with psychological resilience on a sample of 11th grade students (n= 150): 50 male, 100 female in Al-Sharqiya North at Sultanate of Oman during coronavirus pandemic. Descriptive design was used. Findings show that there is a positive relationship (α ≤ 0.05) between students’ Optimism level & psychological resilience level. There is a negative relationship (α ≤ 0.05) between students’ Pessimism level & psychological resilience level. There is no statistically significant differences in Optimism & Pessimism level by gender variable (male, female), No statistically significant differences in psychological resilience level by gender variable (male, female). The importance of the psychological counselor role inside the school by giving lectures about optimism and psychoplasticity and their relation to students. Additionally, the psychological counselor can talk about the results of pessimism.